2014
DOI: 10.3171/2014.6.focus1454
|View full text |Cite
|
Sign up to set email alerts
|

Seizure outcomes following radiosurgery for cerebral arteriovenous malformations

Abstract: Object Seizures are a common presentation of cerebral arteriovenous malformations (AVMs). The authors evaluated the efficacy of stereotactic radiosurgery (SRS) for the management of seizures associated with AVMs and identified factors influencing seizure outcomes following SRS for AVMs. Methods A systematic literature review was performed using PubMed. Studies selected for review were published in Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 67 publications
2
33
2
1
Order By: Relevance
“…6 The present study conflicts with prior studies, which reported superior rates of posttreatment seizure control in patients with obliterated AVMs compared with those with patent AVMs. Hoh et al compared the seizure outcomes following multimodality treatment of 141 patients with seizures to 283 patients without seizures and found obliteration to be significantly associated with Engel Class I outcomes (p < 0.001).…”
Section: Effect Of Radiosurgery On Seizures Outcomes For Patients Witcontrasting
confidence: 56%
“…6 The present study conflicts with prior studies, which reported superior rates of posttreatment seizure control in patients with obliterated AVMs compared with those with patent AVMs. Hoh et al compared the seizure outcomes following multimodality treatment of 141 patients with seizures to 283 patients without seizures and found obliteration to be significantly associated with Engel Class I outcomes (p < 0.001).…”
Section: Effect Of Radiosurgery On Seizures Outcomes For Patients Witcontrasting
confidence: 56%
“…[22][23][24][25] Radiosurgery is a minimally invasive modality for the treatment of AVMs, and it is especially favorable, relative to microsurgery, for small-to moderate-sized AVMs in eloquent or deep brain areas. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] The results of many previous radiosurgery series are confounded by the inclusion of patients who were previously treated with surgical resection, embolization, and fractionated radiation therapy. Thus, comparing the outcomes of these unfiltered studies to those of the interventional arm of ARUBA cannot lead to generalizable conclusions.…”
Section: February 2016mentioning
confidence: 99%
“…This estimate does not account for other neurological sequelae originating from a patent AVM, such as seizures and focal deficits secondary to chronic vascular steal. 27,38,[53][54][55][56][57] …”
Section: February 2016mentioning
confidence: 99%
“…Additionally, DAVF with cortical venous drainage may be less responsive to radiosurgical treatment [14]. Due to the relatively low number of treated patients, the outcomes of DAVF radiosurgery have not been analyzed with the same rigor as those of radiosurgery for cerebral arteriovenous malformations [15][16][17][18][19][20][21][22][23][24][25]. Therefore, the effect of prior embolization on DAVF is poorly understood [26][27][28][29].…”
Section: Discussionmentioning
confidence: 96%